2014
DOI: 10.4103/0970-9290.147113
|View full text |Cite
|
Sign up to set email alerts
|

Strain gauges′s analysis on implant-retained prosthesis′ cast accuracy

Abstract: The splinting technique was considered to be as efficient as the conventional technique. The strain gauge methodology was accurate for strain measurements and cast distortion evaluation. There was no correlation between strain and marginal misfit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Twenty‐two articles combined at least two techniques to correlate implant‐framework misfit and mechanical/biological/clinical consequences, including strain/stress in the mechanical components and peri‐implant bone (21 articles) 72,82‐101 and bacterial counting (1 article) 102 . Within the 21 in vitro studies, 2D assessment using microscopy or SEM has been associated with PSA (5 studies), 85,88,89,91,92 SGA (7 studies), 82‐84,86,93,100,101 FEA (3 studies), 96,97,99 and reverse torque test (2 studies) 87,90 . Two studies combined 3D assessments (optical scanner) with SGA 94,95 and another 2 studies combined SGA and FEA 72,103 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐two articles combined at least two techniques to correlate implant‐framework misfit and mechanical/biological/clinical consequences, including strain/stress in the mechanical components and peri‐implant bone (21 articles) 72,82‐101 and bacterial counting (1 article) 102 . Within the 21 in vitro studies, 2D assessment using microscopy or SEM has been associated with PSA (5 studies), 85,88,89,91,92 SGA (7 studies), 82‐84,86,93,100,101 FEA (3 studies), 96,97,99 and reverse torque test (2 studies) 87,90 . Two studies combined 3D assessments (optical scanner) with SGA 94,95 and another 2 studies combined SGA and FEA 72,103 .…”
Section: Resultsmentioning
confidence: 99%
“…Three SGA studies found vertical misfit positively correlated with peri‐implant 83 and framework strains 82,100 . Two other studies showed no correlation between vertical misfit and strains within the framework or the implants 86,93 . A study tried to correlate the fatigue behavior of the prosthesis to the vertical misfit with the aid of FEA, but no direct relationship was found 96 …”
Section: Resultsmentioning
confidence: 99%
“…However, the other articles examined in this study suggest that the magnitude of the marginal misfit is not a reliable indicator in the prognosis of the stresses generation, once the stress distribution is more related to other factors such as screw tightening. [ 29 33 36 ]…”
Section: Resultsmentioning
confidence: 99%
“…The average of 100 μm was only exceeded in three studies: Barros et al . :[ 5 ] 108 μm; Rodrigues et al ., 2014:[ 36 ] 110 μm; and Tramontino et al . :[ 29 ] 118 μm.…”
Section: Resultsmentioning
confidence: 99%
“…The strain gauge assesses strains induced into a loaded structure by converting the change in resistance of an electric wire into strain measurement. (28 ) The wire used for the strain gauges was insulated by a packing material as a protection from humidity, which was reported to be essential for obtaining reliable recordings (29,30) The first molar was chosen for loading in the posterior region because maximum occlusal forces are often exerted in this area where there is maximum contraction of all elevator muscles. (31) Loading was done with 100 N as a moderate average level of biting force with implant retained overdenture.…”
Section: Discussionmentioning
confidence: 99%